A graphene oxide-mediated polyelectrolyte with high ion-conductivity for highly stretchable and self-healing all-solid-state supercapacitors. Issue 40 (1st October 2018) - Jin, Xuting; Sun, Guoqiang; Yang, Hongsheng; Zhang, Guofeng; Xiao, Yukun; Gao, Jian; Zhang, Zhipan; Qu, Liangti
Abstract : New polyelectrolytes based on polyacrylic acid cross-linked by methacrylated graphene oxide enable the fabrication of self-healing supercapacitors and stretchable supercapacitors. Abstract : Conventional polymer electrolytes are generally limited in ionic conductivity and are short of extra functions, thereby precluding their usage in developing functional all-solid-state energy-related devices. Herein, we design a highly conductive polyelectrolyte (ionic conductivity up to 7.16 S m −1 ) based on polyacrylic acid cross-linked by methacrylated graphene oxide (MGO-PAA) with excellent stretchability (950% strain) and self-healing capability, enabling the direct fabrication of self-healing supercapacitors and stretchable supercapacitors of up to 300% deformation without the extra addition of other self-healing or stretchable materials. This work provides new insights into the synthesis of highly conductive and multifunctional polyelectrolytes and promotes the development of all-solid-state SCs with high energy densities for practical applications in flexible and wearable electronics.